Pengenalan Rukun Islam untuk Anak dalam Hadis di Era Digital - Nur Hafidz; Abda Billah Faza Muhammadkan Bastian; Hasyim Wibowo (Institut Agama Islam Negeri Madura, 2022)
The digital era that is rapidly developing has made Muslims have to be literate with their present presence. In fact, parents are often clueless and need their children to learn to apply the pillars of Islam in understanding digital. Moreover, the context of the study of the hadith of the prophet Muhammad Saw. The presence of digital in providing experiences to children in the form of spirituality, namely the pillars of Islam through electronic media, televisions, smartphones, tablet devices and various other applications. The pillars of Islam as the main foundation that must be introduced are reading the creed, praying, fasting, paying zakat, and pilgrimage. The five pillars of Islam already exist in the saheeh hadith of the prophet Muhammad. So with this digital era children will be moved to learn the pillars of Islam and moved to seek new experiences. From here, parents and teachers become the task of designing learning and accompanying them by introducing digital-based Islamic pillars. The introduction of the pillars of Islam can be done through the Whatsapp application as communication for parents and children, YouTube as a medium for children's learning, the Umma application as a basis for Islamic information. This article analyzes in depth the concept of introducing the pillars of Islam through digital media. This study uses a descriptive analysis of the hadith collection data relating to the introduction of the pillars of Islam for children in the perspective of the hadith of the Prophet Muhammad. The challenge for parents and teachers is to always accompany, supervise, provide children's skills, and give appreciation to children. So that the potential of children's spiritual intelligence is based on the hadith of the Prophet Muhammad with this digital base.